Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3325/cmj.2009.50.55
|View full text |Cite
|
Sign up to set email alerts
|

Daily Mini Quizzes as Means for Improving Student Performance in Anatomy Course

Abstract: 55www.cmj.hr Aim To evaluate daily-written 10-question quizzes in a medical anatomy course as a way to integrate assessment into the course and to evaluate their effect on the course success.Methods Students answering correctly 8/10 or more questions were awarded 0.5 points per quiz. There were 34 quizzes with a maximum point score 17. Measurable outcomes of academic progress in anatomy course (pass rates on 4 examination terms, total pass rate, and average marks) were calculated, and 2007/08 academic year was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 9 publications
0
31
0
1
Order By: Relevance
“…Team work has been shown to facilitate active learning as promotion of a deep approach as students were more engaged when discussing topics together (Vasan & DeFouw, 2005). The role of assessment has been investigated and in an example where daily mini-quizzes were used they were found to significantly improved exam performance (Poljicanin et al, 2009). However, whether this can be attributed to a deep-or strategic approach is debatable.…”
Section: Approach To Learningmentioning
confidence: 99%
“…Team work has been shown to facilitate active learning as promotion of a deep approach as students were more engaged when discussing topics together (Vasan & DeFouw, 2005). The role of assessment has been investigated and in an example where daily mini-quizzes were used they were found to significantly improved exam performance (Poljicanin et al, 2009). However, whether this can be attributed to a deep-or strategic approach is debatable.…”
Section: Approach To Learningmentioning
confidence: 99%
“…Students who had the opportunity to participate in formative assessment exercises, either formative quizzes (Kibble, 2007;Dobson, 2008;Poljicanin et al, 2009;Lee et al, 2012) or mid-term examinations (Carrillo-de-laPeña et al, 2009), performed better on the respective summative examinations relative to students who did not experience such formative feedback. It has been demonstrated that mean formative quiz performance can have a significant, positive correlation to summative examination performance (Dobson, 2008;Poljicanin et al, 2009;Kibble et al, 2011;Lee et al, 2012;Marden et al, 2013). Moreover, Krasne et al (2006) observed that formative assessments that provoked higher order learning, such as the integration and application of knowledge, were more predictive of summative examination performance when compared to formative assessments of lower levels of learning (factual recall, image recognition).…”
Section: Introductionmentioning
confidence: 99%
“…A well-designed curriculum, teaching and learning activities and assessment methods are essential for better academic performance of the students [6][7][8]. Inclusion of DISCUSSION quizzes along with regular assessment methods has been suggested by earlier studies [9]. Quizzes were reported as best tools to encourage and monitor students [10].…”
Section: Resultsmentioning
confidence: 99%